PENGARUH IKLAN TELEVISI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK MEREK WARDAH DI KOTA PALU - RISKIANA, SITI (Fakultas Ekonomi Universitas Tadulako, 2017)
The purpose of this study is to know and analyze the influence of television advertising and brand image simultaneously and partially to the purchase decision of Wardah brand product in Palu City. The variables of this research are television advertisement (X1) and brand image (X2). While the dependent variable is the purchase decision (Y). The research method used is descriptive method causal with the number of sample 75 people. Form of sampling using purposive sampling technique. Data analysis method used in this research is multiple linear regression analysis method. The results showed that: 1). Television advertisement and brand image simultaneously have a significant effect on the purchasing decision of Wardah brand products; 2). Television advertisement partially significant effect on purchasing decision of Wardah brand product; 3). Brand image partially significant effect on purchasing decision of Wardah brand product in Palu City.